Design and Analysis of Quality Improvement for Radiator Manufacturing Industry - Johan George Cherian; Premjith S.; Abin Paul; Mamitha T. Mathew (International Journal of Energy and Thermal Applications, 2024)
This study investigates the design and analysis of quality control measures for the radiator manufacturing industry through the utilization of various nanofluids. Both experimental techniques and computational fluid dynamics (CFD) simulations using ANSYS software are employed to assess the performance of different nanofluids in enhancing the efficiency and reliability of radiators. The experimental aspect involves testing the heat transfer characteristics and thermal conductivity of nanofluids, while CFD simulations provide insights into fluid flow behaviors within radiator systems. By combining these approaches, a comprehensive understanding of the impact of nanofluids on radiator performance is achieved, facilitating the development of effective quality control strategies. The findings from this research contribute to advancing the utilization of nanofluids in radiator manufacturing processes, potentially leading to a more efficient and durable radiator system.
Keywords: Ansys; CFD; Nanofluids; Radiator